AN ERROR ANALYSIS OF USING DEGREES OF COMPARISON IN STUDENTS’DESCRIPTIVE WRITING AT THE SEVENTH GRADE OF SMP KESUMA BANGSA DEPOK - Christanto Dwi Nugroho (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2019)
ABSTRACT The objective of this study is to analyze the error of using Degrees of Comparison at the seventh grade of SMP Kesuma Bangsa Depok.The technique was made of purposive sampling, the sample was 40 students. The method of the research was descriptive qualitative as for the technique of collecting data was test method. The writer applied the test as research instrument. The data was described as a percentage by using percentage analysis. The writer discover there are some errors in students’ descriptive writing initiated with subject 6,27%, to be 25,46%, adjective 17,71%, article 7,01%, spelling 8,59%, noun 2,58%, pronoun 9,23%, preposition 1,85%, word choice 2,58%, capitalization 14,39%, conjunction 2,58%, and word order 1,85%. The most frequent errors are to be 25,46%, adjective 17,71%, and capitalization 14,39%. The causes of errors are due to first language interference and translation. In conclusion, it might be deduced that there are errors of using Degrees of Comparison in students’ descriptive writing at the seventh grade of SMP Kesuma Bangsa Depok.Abstrak Tujuan dari penelitian ini menganalisa kesalahan penggunaan perbandingan pada karangan deskriptif siswa kelas VII SMP Kesuma Bangsa Depok, menggunakan teknik pengambilan sample sebanyak 40 siswa. Metode yang digunakan pada penelitian ini adalah deskriptif kualitatif, dan teknik pengumpulan data. Peneliti menggunakan tes instrument. Data digambarkan dengan analisa persentasi. Peneliti menemukan ada beberapa kesalahan penulisan deskriptif siswa yaitu subyek 6.27%, kata kerja 25,46 %, kata sifat 17,71%, kata depan 7,01%, ejaan 8.59%, kata benda 2.58%, kata pengganti 9.23%, awalan 1.85%, pemilihan kata 2.58%, huruf kapital 14.39%, kata penghubung 2.58% and tata letak kata 1.85%. kesalahan yang sering terjadi adalah kata kerja sebanyak 25,46%, kata sifat 17,71 % dan huruf capital 14.39% . penyebab kesalahan terjadi pengaruh Bahasa pertama dan terjemahan. Didapat kesimpulan bahwa ada kesalahan pada karangan deskriptif siswa kelas VII di SMP Kesuma Bangsa.